2022
DOI: 10.3390/universe8110562
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric TEC Forecasting over an Indian Low Latitude Location Using Long Short-Term Memory (LSTM) Deep Learning Network

Abstract: The forecasting of ionospheric electron density has been of great interest to the research scientists and engineers’ community as it significantly influences satellite-based navigation, positioning, and communication applications under the influence of space weather. Hence, the present paper adopts a long short-term memory (LSTM) deep learning network model to forecast the ionospheric total electron content (TEC) by exploiting global positioning system (GPS) observables, at a low latitude Indian location in Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Te developed model results were collated with the IRI and NeQuick-2 models and it shows that the observed LSTM model produces reliable results [14]. Reddybattula et al [15] developed a deep learning model to forecast the TEC during the 24 th solar cycle based on data from the low latitude IISC station. Te predicted TEC data were justifed with the IRI 2016 model and it was found that the deep learning model results closely matched the true TEC values.…”
Section: Introductionmentioning
confidence: 99%
“…Te developed model results were collated with the IRI and NeQuick-2 models and it shows that the observed LSTM model produces reliable results [14]. Reddybattula et al [15] developed a deep learning model to forecast the TEC during the 24 th solar cycle based on data from the low latitude IISC station. Te predicted TEC data were justifed with the IRI 2016 model and it was found that the deep learning model results closely matched the true TEC values.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of neural network models in ionospheric prediction has garnered increasing attention from researchers, as evidenced by successful applications documented in the recent literature [35][36][37][38]. Notably, many ionospheric grid point-prediction models have been developed using deep learning techniques, including recurrent neural networks (RNNs), LSTM, and GRU architectures [39][40][41][42][43][44], etc. These methods effectively capture the nonlinear characteristics of time series data, thereby enhancing prediction accuracy, as corroborated by various studies.…”
Section: Introductionmentioning
confidence: 99%
“…Proper BM ensures optimal charging and discharging cycles, safeguards against overcharging or deep discharging, and monitors critical parameters like voltage, current, and temperature [3]. These parameters are crucial as they impact the battery's health and, by extension, the vehicle's reliability [4]. Moreover, thermal management within the battery system is vital to prevent overheating, which can lead to reduced battery life or, in extreme cases, pose safety risks.…”
Section: Introductionmentioning
confidence: 99%